Tinjauan Hukum Islam Terhadap Pengelolaan Dana Simpan Pinjam Di Serikat Takaful Guru Damrong Wittaya School (Bannangseta Yala Thailand Selatan) - Bunga, Mr Abdulsalam, Nurul Huda M. Ag (2017)
The purpose of this study was to determine the savings and loan fund in Takaful Sarikat Damrong Wittaya School Teachers (Bannangseta, Yala, southern Thailand) under Islamic law. This research is a field research with qualitative approach. The methods used in data collection was by observation, interview and documentation. The analysis is a method Deductive and inductive methods. The results of this study, it can be concluded that (1) Management of Funds Deposits consisting of Management with the principle of Mudharabah, and Wadiah complies with Islamic law, because it has sufficient criterion in terms of the definitive, application in the field, and in terms of the practices will be undertaken by takaful teachers' union. (2) The management of loan funds with Takaful Master Damrong Wittaya School, conducted by two principles, namely the principles of Murabahah and principles Qardhu Al Hasan. In practice murabaha conducted in accordance with the principles of Islamic law because there was an agreement between the seller in this case carried out by the union with the buyers. While in practice Qardhu Al Hasan was also in conformity with Islamic law because the intention of the union in helping others and giving dried on gradually without any additional payment by money at all.